A synbiotic mixture of scGOS/lcFOS and Bifidobacterium breve M-16V increases faecal Bifidobacterium in healthy young children - P. Kosuwon (2018)
© 2018 Wageningen Academic Publishers. Little is known about the impact of nutrition on toddler gut microbiota. The plasticity of the toddler gut microbiota indicates that nutritional modulation beyond infancy could potentially impact its maturation. The objective of this study was to determine the effect of consuming Young Child Formula (YCF) supplemented with short chain galactooligosaccharides and long chain fructooligosaccharides (scGOS/lcFOS, ratio 9:1) and Bifidobacterium breve M-16V on the development of the faecal microbiota in healthy toddlers. A cohort of 129 Thai children aged 1-3 years were included in a randomised controlled clinical study. The children were assigned to receive either YCF with 0.95 g/100 ml of scGOS/lcFOS and 1.8×107cfu/g of B. breve M-16V (Active-YCF) or Control-YCF for 12 weeks. The composition and metabolic activity of the faecal microbiota, and the level of secretory immunoglobulin A were determined in the stool samples. The consumption of Active-YCF increased the proportion of Bifidobacterium (mean 27.3% at baseline to 33.3%, at week 12, P=0.012) with a difference in change from baseline at week 12 between the Active and Control of 7.48% (P=0.030). The consumption of Active-YCF was accompanied with a more acidic intestinal milieu compared to the Control-YCF. The pH value decreased statistically significantly in the Active-YCF group from a median of 7.05 at baseline to 6.79 at week 12 (P < 0.001). The consumption of Active-YCF was associated with a softer pudding-like stool consistency compared to the Control-YCF. At week 6 and week 12, the betweengroup difference in stool consistency was statistically significant (P=0.004 and P < 0.001, respectively). A Young Child Formula supplemented with scGOS/lcFOS and B. breve M-16V positively influences the development of the faecal microbiota in healthy toddlers by supporting higher levels of Bifidobacterium. The synbiotic supplementation is also accompanied with a more acidic intestinal milieu and softer stools.